PERBANDINGAN EFEKTIVITAS MODEL GAME BASED LEARNING BERBANTUAN WORDWALL DAN PEMBELAJARAN KONVENSIONAL TERHADAP HASIL BELAJAR MATERI PECAHAN KELAS V SEKOLAH DASAR: Penelitian Eksperimen - Aisyah Putri Siregar; Syafri Ahmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the limited implementation of innovative learning models and interactive technology-based instructional media in mathematics classrooms. The research aimed to examine the differences in students’ mathematics learning outcomes on the topic of fractions between those taught using the Game-Based Learning model supported by Wordwall media and those taught through a conventional learning approach. The study was conducted in Grade V at SDN 01 Situjuah Gadang as the experimental class and SDN 03 Situjuah Gadang, Lima Puluh Kota Regency, as the control class. A quasi-experimental design involving pretest and posttest assessments was employed. Data were analyzed using descriptive and inferential statistics, including normality, homogeneity, and hypothesis testing. The pretest results showed that the experimental class obtained a mean score of 53.5, while the control class achieved 52.5, with t statistic = 0.300 < t table = 2.024 and Sig. (2-tailed) = 0.766 > 0.05, indicating no significant difference between the groups before treatment. After the intervention, the posttest mean scores increased to 84.5 for the experimental class and 57.0 for the control class, with t statistic = 4.102 > t table = 2.024 and Sig. (2-tailed) = 0.008 < 0.05. These findings indicate that the null hypothesis was rejected and the alternative hypothesis was accepted. Therefore, the use of the Game-Based Learning model assisted by Wordwall media resulted in significantly better learning outcomes than the conventional teaching approach in learning fractions.